MANAGING WORK PRODUCTIVITY THROUGH GLOBAL COMPETENCE - Bambang Haryanto; Candra Darmawan (Yonetim Jurnal, 2022)
This research was conducted to determine the role of global competence in practice in the industrial world on work productivity with motivation as a moderating variable that influences it with this type of applied research using quantitative methods Partial Least Square Structural Equation Model (PLS-SEM) explaratory prediction using SmartPLS software , the results of the research In this case, there is a significant effect between Global Competence on Work Productivity, while for the motivation variable as a moderating Global Competence on work productivity, it has a very small effect, namely 0.817 but has no effect at a significant level of 0.005.